Determining selected factors of personal bankruptcy in Malaysia / Wan Hafawati Nadhirah Wan Salleh - Wan Salleh, Wan Hafawati Nadhirah (Faculty of Business Management, 2017)
Cost of living is increasing as the economy is not so good recently. People facing the stress of arising the living cost every year. The living cost was seen as the causes people consume with the debt for their life. But the debt of loan and credit have bad side view which is it could piling up the debt at unreasonable amount and lead to the unpaid debt. This study is about the factors of increasing number of bankruptcy for the personal cases. Bankruptcy occurred when Malaysians individual have fails to repay the debt or loan above the value which has been set by the government. This study is using time series method for sixty of observation, thus the data ranges are from 2010 to 2014 on a monthly basis. This study found out four main factors that contribute to the bankruptcy cases as the most popular. The factors are household consumption, car purchasing, personal loan and credit card, while total number of bankruptcy cases as dependent variable. These factors explain why the bankruptcy could occur to the individual status and the risk that the Malaysian individual will face on consuming the selected bankruptcy factors without they are realising. The riskier group of people for this bankruptcy issue is those in early stage on their career. Overall, this was view about the government has reveal that Malaysian cases of bankruptcy has arising each year and giving bad perspective to the fresh graduate entering the working environment. The concern to see the usual loan that switch to debt and credit card debt have significant relationship to the bankruptcy cases in Malaysia